Vascular events are risk factors for anal incontinence in systemic sclerosis: a study of morphology and functional properties measured by anal endosonography and manometry. (October 2014) - Bartosik, I; Andréasson, K; Starck, M; Scheja, A; Hesselstrand, R
<x xml:space="preserve">Abstract</x> Objectives: To study anal sphincter morphology, anal sphincter pressure, and rectoanal inhibitory reflex (RAIR) in patients with systemic sclerosis (SSc) complicated by anal incontinence (AI) and to investigate possible risk factors for AI in SSc. Method: Nineteen SSc patients with severe AI were investigated using anal endosonography, anal manometry, and rectal manovolumetry. To determine risk factors for AI, disease characteristics of SSc patients with AI were compared with those of 95 SSc patients without AI; there were five matched SSc patients without AI for each SSc patient with AI. Results: The mean (SD) internal sphincter thickness was 1.3 (0.46) mm in patients with AI, which was thinner (p < 0.001) than reference data from healthy individuals whose internal sphincter measured 2.2 (0.45) mm, whereas the external sphincter thickness did not differ. The mean (SD) resting pressure in AI patients was lower than the reference data from healthy individuals [60 (22) vs. 94 (29) mmHg, p < 0.002] whereas the squeeze pressure did not differ. Centromeric antibodies and features of vascular disease [i.e. the presence of pulmonary arterial hypertension (PAH), digital ulcers, pitting scars, or the need for iloprost infusions] were associated with AI whereas fibrotic manifestations [i.e. modified Rodnan skin score (mRss), the diffuse cutaneous SSc (dcSSc) subset, or low vital capacity (VC)] were not. Conclusions: SSc patients with AI have a thin internal anal sphincter and a low resting pressure. Risk factors for AI among SSc patients are centromeric antibodies and vascular disease, which supports the hypothesis that gastrointestinal involvement in SSc is in part a vascular manifestation of the disease.